Keefektifan Model Problem Based Learning Berbantuan Media Blooket Terhadap Kemampuan Pemecahan Masalah Siswa Kelas V Sekolah Dasar - Garini Lituhayu; Noening Andrijati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to to examine how students’ problem-solving skills related to LCM and GCD are influenced by the implementation of a problem-based learning model supported by the Blooket platform. This study employed a non-equivalent control group design and a quantitative quasi-experimental method. All fifth-grade students in the Wijaya Kusuma Cluster constituted the study population, and 28 students were selected as the sample for the control and experimental groups. Tests and documentation were some of the methods used to collect data. The independent samples t-test, N-Gain test, homogeneity test, and normality test were used to analyze the data. With a significance value  of 0.000 (< 0.05), the study's findings show that students' problem-solving abilities are significantly impacted by the use of the Problem-Based Learning paradigm with the help of the Blooket platform. In addition, the N-Gain score of 0.70 indicates that the students' skills have improved significantly. Therefore, it has been shown that the Blooket platform-supported Problem-Based Learning model is superior to traditional learning in improving students' problem-solving abilities.